American teaching and practice of industrial engineering and management - Cherry, J. (College of Aeronautics, 1956)
In June 1954 a small mission, comprising T.B.Worth, A.M.I.E.E., M.I.Prod.E., F.R.S.A., Principal Senior Lecturer in Production Engineering and Assistant Head of the Department of Mechanical and Production Engineering at Birmingham College of Technology, K.J.Shone, M.A. (Cantab),A.M.I.Mech.E., M.I.Ear.E., M.E.I.C., Head of Department of Industrial Administration, Royal Technical College, Glasgow, and the author, visited the United States of America to "observe and gain experience of American methods of training in Industrial Engineering and Management both in universities and industrial plants". Subsequently, in September, D.M,Williams, Ph.D., B.Sc., (H.M.I.) joined the mission, which returned in November 1954. Each member investigated different aspects and separate reports are being presented. This report deals mainly with education in Industrial Engineering. Other Sections, dealing with education in Management, Industrial Engineering and Management in Industry, Research and Consultancy will be presented subsequently by the author. Education in Industrial Engineering in the U.S.A. laid emphasis on the need for sound education in the bagic and engineering sciences prior to the study of Industrial Engineering subjects. Considerable attention was paid to the economic aspects of industry and subjects such as Engineering Economic Analysis were prominent. Awareness of the impact of new developments in the industrial engineering field was also evident and curricula were being revised to introduce subjects such as Electronic Theory into the electrical programme, and the application of Operations Research techniques'to the mathematics programme. The value of formal education in Industrial Engineering was acknowledged by most industrialists, who were absorbing I.E. graduates at a rate exceeding 1500 per annum.- In 1954 there were approximately 8,000 students enrolled in. I.E. courses. A comparison of equivalent courses in Great Britain showed that less than 50 students were enrolled. The comparison also revealed the inadequacy of the Higher National Certificate courses in Production Engineering, and a strong plea is made for more facilities for students to take Higher National Diploma courses in Production Engineering.